Triphenylamine substituted copper and zinc phthalocyanines as alternative hole-transporting materials for solution-processed perovskite solar cells - Celik, Gizem Gumusgoz; Sahin, Ayse Nur; Lafzi, Ferruh; Saracoglu, Nurullah; Altindal, Ahmet; Gurek, Ayse Gul; Atilla, Devrim (ROYAL SOC CHEMISTRY, 2022)
In the present study, new peripheral substituted Zn(II) and Cu(II) phthalocyanine derivatives (p-ZnPc and p-CuPc) bearing bulky aromatic triphenylamine groups were synthesized as alternative hole-transporting materials (HTMs). The structures of the new phthalocyanine derivatives (p-ZnPc and p-CuPc) were illuminated by various spectroscopic techniques such as mass spectrometry and H-1, and C-13-NMR. After structural analysis, their photophysical properties in solution and the solid phase were examined by UV-Vis absorption and fluorescence spectroscopy. Using p-ZnPc and p-CuPc as HTMs, highly stable perovskite-based solar cells with the structure of FTO/SnO2/perovskite/p-ZnPc and p-CuPc/Ag have been developed and characterized. It was observed that our devices with p-ZnPc as the HTM maintain over 93% of the initial performance for more than 960 h under atmospheric conditions (22-27 degrees C) with 35-45% relative humidity. In addition, some strategies such as using various methylammonium iodide (MAI) and lead iodide (Pbl(2)) blend ratios between 1 : 0.4 and 1 : 1.8 were employed to test the effect of the blend ratios on the long term stability of the perovskite-based solar cells. Our findings demonstrated that the spin-coated p-ZnPc based HTM demonstrated competitive power conversion efficiency and exhibited superior stability without encapsulation compared to commonly used HTMs.
Keywords: OPEN-CIRCUIT VOLTAGE; ZN(II) PHTHALOCYANINES; HIGHLY EFFICIENT; LITHIUM-SALTS; PERFORMANCE; LAYERS; RECOMBINATION; STABILITY; Chemistry